Pengaruh Struktur Modal, Persistensi Laba Dan Investment Opportunity Set (IOS) Terhadap Kualitas Laba - Lina Karlina; Ayumi Rahma (CV. ITTC INDONESIA, 2025)
This study aims to analyze whether Capital Structure, Earnings Persistence and Investment Opportunity Set (IOS), both partially and simultaneously affect Earnings Quality in healthcare companies listed on the Indonesia Stock Exchange. The sampling method used is Purposive Sampling, which is a technique that looks at determining the criteria selected as a factor, which obtained a sample of 85 data or 17 companies. The data used is secondary data, namely the financial statements of companies listed on the IDX. In order to prove the hypothesis, multiple regression testing is carried out which begins with the classical assumption test. The research model passed the classic assumption test. Simultaneous testing concluded that all independent variables affect earnings quality. Partial testing of Capital Structure affects Earnings Quality, Earnings Persistence affects Earnings Quality and Investment Opportunity Set (IOS) affects Earnings Quality.